RANCANG BANGUN SISTEM INFORMASI ORGANISASI PADA IKATAN KELUARGA LANGKE REMBONG (IKALABONG) BALI BERBASIS WEB - I NYOMAN BAGUS SUWETA NUGRAHA; I Putu Yoga Bawantara; Frederik Adventus Teren (Jurnal Manajemen dan Teknologi Informasi, 2021)
Organization is a group of people in a container for a purpose together. At the Langke Rembong Bali Family Association, the information processing process is still done manually and some information about the organization is not conveyed properly. To solve this problem, an organizational information system is needed in the Web-based Rembong Bali Family Association to assist the organization's administrators in processing data effectively and efficiently. This web-based organizational information system is built based on concepts extracted from the interview process, literature study and system implementation. The design of this system is made using the PHP, CSS, and HTML programming languages. The Waterfall model is a system development method used in the design of organizational systems. With the condtruction of this system, it is able to provide information to support the right decision making for the future movement of the organization.